Too sweet to be good - Jackson, K. M (Jackson, K. M. Sugar Lake novel., 2019)
Alexandrea Gale put her acting career on hold to help keep her family<U+2019>s bakery in business<U+2014>and gave it a few eye-catching updates while she was at it. To earn money to return to New York, she puts her design skills to work with a job renovating a once thriving local vintage theater. But Alexandrea didn<U+2019>t bargain on the owner<U+2019>s business-minded grandson fighting her every step of the way<U+2014>or proving so unexpectedly irresistible . . . As the new head of his family<U+2019>s real estate business, Kellen Kilborn feels that selling the theater is the only way to do right by the grandmother who helped raise him. He just can<U+2019>t take a risk on Alexandrea<U+2019>s inventive ideas<U+2014>but he also can<U+2019>t walk away from her warm-hearted free spirit. As troubling decisions threaten to tear them apart, can they create a way to turn their dreams into the sweetest of futures together?